Applying John Dewey’s Constructivism in the Merdeka Curriculum: A Conceptual Analysis - Nafidatun Nisa; Ahmad Hadi Pranoto; Erlina Laily Nur Afifa; Oseolla Savana; Agus Sutiyono (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
This article aims to analyze the constructivism theory paradigm developed by John Dewey and explore its relevance to implementing the Merdeka Curriculum in Indonesia. Dewey's theory of constructivism emphasizes the importance of direct experience and reflection in active learning, where students construct knowledge through interaction with the real world. The method used in this research is a literature review, which involves analyzing Dewey's main texts related to constructivism theory and documents and policies related to the Merdeka curriculum. The analysis technique is carried out by comparing Dewey's principles of constructivism with the characteristics of Merdeka curriculum which focuses on flexibility, freedom of learning, and the development of 21st century skills. The results show that Dewey's principles of constructivism, such as experiential learning, collaboration, and reflection, are very relevant and can be applied in Merdeka curriculum to create a more innovative and student-centered learning environment and the importance of students' freedom to learn according to their potential and interests.